Not just science : questions where Christian faith and natural science intersect - Chappell, Dorothy F., 1947-; Cook, E. David (Edward David), 1947- (Grand Rapids, Mich. : Zondervan, 2005)
"A look at the questions students should be asking as they study the natural sciences in relation to the Christian worldview and think critically about God's creation"--Provided by publisher.
Includes bibliographical references.
Keywords: Religion and science